Augmented Reality in Higher Education: A Bibliometric Analysis of Research Trends and Evolution from 1997 to 2024 - Sindy Kania Sulastri (Journal of Technology-Assisted Learning, 2025)
Augmented reality (AR) is a technology that superimposes digital content onto the physical world, blending virtual components like images, videos, and 3D models with real environments. In the realm of higher education, AR-based learning presents significant benefits. This research seeks to examine and illustrate studies on AR in the context of higher education. Data were obtained from the Scopus database, focusing on AR-related publications, which were analyzed and visualized using Biblioshiny. The article selection process in bibliometric analysis followed the PRISMA diagram. The analysis examined various bibliographic factors, including countries, institutions, journals, authors, publications, and frequently co-occurring keywords. A total of 832 articles meeting the inclusion criteria were analyzed, covering the period from 1997 to 2024. Research in this field has expanded significantly, with a notable rise in publications since 2015. The article by Akçayir M, published by Elsevier in the Educational Research Review journal in 2017, has the highest total citations, with 1309 citations. The United States and China emerged as the leading contributors to this area of study. The university with the most publications is led by the University of Bologna in Italy. Key research themes in AR for higher education include education, computer science, and technology. This article also highlights emerging research trends and the evolution of AR concepts in the educational domain, with a particular focus on higher education.